Utility of the ITS1 region for phylogenetic analysis in stingless bees: A case study of the endangered Melipona yucatanica Camargo, Moure and Roubik (Apidae: Meliponini) - Ruiz Carreira, C. (2017)
The internal transcribed spacers of the ribosomal RNA gene have been recently proposed as an appropriate marker for genetic analysis of the molecular variation of stingless bees. Herein we report the characterization of the complete ITS1 region in two populations (from Mexico and Guatemala) of the endangered Melipona yucatanica Camargo, Moure and Roubik. Phylogenetic analyses showed low genetic variation between populations but defined a geographic structure with Mexican and Guatemalan specimens forming two well supported clades. Low ITS1 genetic variation found between populations contrasts with high genetic variation found in other markers. Phylogenetic analysis corroborates the inclusion of M. yucatanica within the subgenus Melipona sensu stricto based on previous morphological studies. The results highlight the utility of the ITS1 for the characterization of stingless bee populations.